2020
DOI: 10.5688/ajpe8421
|View full text |Cite
|
Sign up to set email alerts
|

Report of the 2020 Special Committee on Substance Use and Pharmacy Education

Abstract: Education Report (SAPER) specifically with recommendations on core curricular content and delivery processes on substance misuse and substance use disorder (SUD). This report provides information on the committee's process to address the charges, background information and resources pertaining to the charges, and rationale for SUD being a critical topic for curriculum at colleges and schools of pharmacy. This committee offers several recommendations to the Association of Colleges of Pharmacy (AACP) pertaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Student education and school/curriculum were frequently mentioned under the education and sources domains, reaffirming the importance of guidance from organizations such as AACP in SUD/OUD and pharmacy education. 18 Pharmacists and pharmacy schools would benefit from our results, including recognition of how stigma and bias contribute to poor health outcomes for individuals with SUD/OUD and a notable lack of acknowledgement of social determinants of health impacting the opioid crisis, as students are educated to combat the crisis. This study documents what student pharmacists are learning about the opioid crisis, practices they are seeing, and belief sets that influence pharmacy experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Student education and school/curriculum were frequently mentioned under the education and sources domains, reaffirming the importance of guidance from organizations such as AACP in SUD/OUD and pharmacy education. 18 Pharmacists and pharmacy schools would benefit from our results, including recognition of how stigma and bias contribute to poor health outcomes for individuals with SUD/OUD and a notable lack of acknowledgement of social determinants of health impacting the opioid crisis, as students are educated to combat the crisis. This study documents what student pharmacists are learning about the opioid crisis, practices they are seeing, and belief sets that influence pharmacy experiences.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,16,17 Students' lack of perspective is notable given that most academic institutions have a focus on SDOH and may indicate that current practitioners share the same lack of recognition; this phenomenon would likely contribute to the stigma towards patients with OUD. 18 Opioid manufacturers have faced lawsuits citing their responsibility in the crisis. Industry has been implicated as a contributing factor to the opioid crisis, through incentives to prescribers, false advertising, and aggressive product marketing without disclosing addictive nature.…”
Section: A J P Ementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence demonstrates that inadequate training and lack of confidence in communicating about naloxone are barriers to higher dispensing rates by practicing pharmacists 13,14 . Furthermore, recent recommendations from the American Association of Colleges of Pharmacy indicate that naloxone counseling and overdose management should be core components of the Doctor of Pharmacy curriculum 15 . The current literature highlights several innovative naloxone training programs; however, the majority focus on student's perceived self‐efficacy in counseling as the primary outcome 8‐11 …”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the American Association of Colleges of Pharmacy's (AACP) Special Committee on Substance Use and Pharmacy Education stated, "Experiential opportunities to apply foundational SUD knowledge in clinical environments must be developed and supported." 3 A 2015 survey of 75 AACP member schools found that 79% provided at least two hours of required didactic content related to SUD and 30% provided at least four hours. 4 However, advanced pharmacy practice experiences (APPEs) focused on SUD treatment were available in only 23% of programs and even then were offered to a mean of only 2.6 students each year.…”
Section: Introductionmentioning
confidence: 99%